Technological properties of rock aggregates - Johansson, Eva (Luleå tekniska universitet, Geoteknologi, 2011)
The commission of technical geology is to apply geological knowledge to the field of constructional engineering, mining technology, environmental protection, architecture etc. The sector of infrastructure is highly dependent on the production of crushed rock materials as the main constituent of e.g. road and railway constructions. The functional properties of crushed rock materials used are of major importance concerning the durability of the construction and they are strongly connected to economic and environmental consequences. The quality of the aggregates is the crucial agent to reach the optimal performance of the infrastructural network. Due to the geological, geographic and climatologic preconditions of Northern Scandinavia, the quality of crushed rock materials is even more important. The Fennoscandian bedrock is dominated by igneous and metamorphic rocks. The access to qualitative rocks for production of aggregates displays considerable regional variation. The oblong geographical extension of the North Scandinavian countries, the fairly low population and the frequent traffic require the widespread infrastructure. The temperate climate characterized by freeze-thaw cycles combined with usage of studded tyres requires a long lasting construction of high sustainability.In spite of available international standards dealing with the aggregates’ quality, the deterioration of the road constructions is noted in Sweden; it is mostly caused by use of mica-rich, heterogeneous rocks. The utilization of these kinds of rock materials as base courses and bituminous wearing courses results in economic losses and negative environmental consequences.The aim of the present thesis was to study technological properties of aggregates in a challenge to connect them with the petrographic characteristics of rock materials. The study includes an investigation of enrichment of free mica particles in fine fractions originating from crushed rock aggregates and the development of a scientifically based method for estimation of free ...